2010
DOI: 10.1111/j.1475-1313.2010.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

L‐ and M‐cone input to 12Hz and 30Hz flicker ERGs across the human retina

Abstract: We recorded L- and M-cone isolating ERGs from human subjects using a silent substitution technique at temporal rates of 12 and 30 Hz. These frequencies isolate the activity of cone-opponent and non-opponent post-receptoral mechanisms, respectively. ERGs were obtained using a sequence of stimuli with different spatial configurations comprising; (1) circular stimuli of different sizes which increased in 10° steps up to 70°diameter, or (2) annular stimuli with a 70° outer diameter but with different sized central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
5
9
2
Order By: Relevance
“…As mentioned above, this study teased out rod-and medium-to long-wavelength cone subtypespecific contributions to the mouse flicker ERG under identical adaptation conditions. Compared with mice, spectral isolation of individual photoreceptor types in the human retina has received more attention (Bessler et al 2010;Brainard et al 2000;Cao et al 2011;Challa et al 2010;Kremers et al 2000Kremers et al , 2009Kremers and Link 2008;Kremers and Scholl 2001), which has allowed more detailed investigations. Even so, few have examined rod-only contributions to the flicker ERG (Cao et al 2011;Kremers and Pangeni 2012), because its isolation from S-cones with reasonable strength is difficult [i.e., max of S-cone ϳ 435 nm vs. rod ϳ 495 nm (Kraft et al 1993;Stockman and Sharpe 2000)].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, this study teased out rod-and medium-to long-wavelength cone subtypespecific contributions to the mouse flicker ERG under identical adaptation conditions. Compared with mice, spectral isolation of individual photoreceptor types in the human retina has received more attention (Bessler et al 2010;Brainard et al 2000;Cao et al 2011;Challa et al 2010;Kremers et al 2000Kremers et al , 2009Kremers and Link 2008;Kremers and Scholl 2001), which has allowed more detailed investigations. Even so, few have examined rod-only contributions to the flicker ERG (Cao et al 2011;Kremers and Pangeni 2012), because its isolation from S-cones with reasonable strength is difficult [i.e., max of S-cone ϳ 435 nm vs. rod ϳ 495 nm (Kraft et al 1993;Stockman and Sharpe 2000)].…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of the different cone populations therefore offers the possibility of objective assessment of their function in acquired and hereditary ocular pathologies [20,21]. This approach also enables in vivo assessment of cone spectral sensitivities using the ERG [10,[32][33][34] and permits the study of the spatial and relative distributions of the different cone types [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Jacob et al (2015) found that the L:M ratio in highfrequency responses is much larger with FF than with smaller stimuli, indicating that the responses that originate in the periphery are strongly L-cone dominated. This is confirmed in other ERG recordings (Challa et al, 2010;Kuchenbecker, Sahay, Tait, Neitz, & Neitz, 2008; and messenger ribonucleic acid analyses (Hagstrom, Neitz, & Neitz, 1997. The L:M ratio determines the stimulus conditions for isoluminance: The larger the L:M ratio, the smaller the values for F R at isoluminance (because less red modulation is needed to counteract the response to the green light).…”
Section: Discussionsupporting
confidence: 58%